The Effect of Pravastatin Provision on Endotelin-1 Levels in Preeclapmsia’s High Risk Patients - Rizky A Ramadhani1, Deviana SorayaRiu1, Irnawati Bahar1, Isharyah Sunarno1, Retno B. Farid1, Eddy Ha (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: To determine the effect of pravastatin administration on endothelin-1 levels in patients at highrisk of preeclampsia.Method: There are 70 subjects in this research that consist of 34 subjects with the risk of high preeclampsiawho get aspirin and 36 subjects of research to get Aspirin and Pravastatin. Subjects are given therapy startedthe gestational age of 12-19 weeks in 6 days until 36 weeks of pregnancy. Endhotelin-1 levels prior toadministration of therapy compared with the levels of endothelin-1 after the administration of treatment.Results: The test results show the administration of aspirin or aspirin and Pravastatin is shown to provide thechanges were significant at levels of endothelin-1 after the administration of treatment. It is characterized bythe decrease in the levels of endothelin-1 which were significantly (p <0.005). But by assessing percentagedecrease in the provision of aspirin with pravastatin give change levels of endothelin-1 is large (45.74%)compared with administration of aspirin alone (28.8%).Conclusion: From this study it can be concluded that endothelin-1 levels before administration of aspirinand pravastatin were 86.18 ng/L and after administration of 46.76 ng/L. Giving aspirin and pravastatin 20mg in patients with high risk factors of preeclampsia provide reduced levels of endothelin-1 is greater thanthe prevention of preeclampsia that is used when it is only aspirin.